2010
DOI: 10.2119/molmed.2010.00126
|View full text |Cite|
|
Sign up to set email alerts
|

Diet Restriction Inhibits Apoptosis and HMGB1 Oxidation and Promotes Inflammatory Cell Recruitment during Acetaminophen Hepatotoxicity

Abstract: Acetaminophen (APAP) overdose is a major cause of acute liver failure and serves as a paradigm to elucidate mechanisms, predisposing factors and therapeutic interventions. The roles of apoptosis and inflammation during APAP hepatotoxicity remain controversial. We investigated whether fasting of mice for 24 h can inhibit APAP-induced caspase activation and apoptosis through the depletion of basal ATP . We also investigated in fasted mice the critical role played by inhibition of caspasedependent cysteine 106 ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(127 citation statements)
references
References 50 publications
8
116
3
Order By: Relevance
“…Acetaminophen overdose is a well-known cause of DILI (Lee, 2004). A number of animal and human studies have demonstrated that serum HMGB1 is a diagnosis and severity-assessment biomarker of acute liver injury induced by acetaminophen, as well as other drugs (Antoine et al, 2013; Antoine et al, 2012a; Antoine et al, 2010; Dragomir et al, 2011; Gong et al, 2010a; Yang et al, 2012g; Zhou et al, 2011c). HMGB1 release during acetaminophen-mediated liver injury impairs the innate immune response and accelerates the inflammatory response (Scaffidi et al, 2002; Wang et al, 2007a; Wang et al, 2013m).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…Acetaminophen overdose is a well-known cause of DILI (Lee, 2004). A number of animal and human studies have demonstrated that serum HMGB1 is a diagnosis and severity-assessment biomarker of acute liver injury induced by acetaminophen, as well as other drugs (Antoine et al, 2013; Antoine et al, 2012a; Antoine et al, 2010; Dragomir et al, 2011; Gong et al, 2010a; Yang et al, 2012g; Zhou et al, 2011c). HMGB1 release during acetaminophen-mediated liver injury impairs the innate immune response and accelerates the inflammatory response (Scaffidi et al, 2002; Wang et al, 2007a; Wang et al, 2013m).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…It is likely that this protein took the all-thiol form of HMGB1 as it had chemotactic qualities to recruit enterocytes, smooth muscle, and endothelial, and stem cells (32,51,74,81,99,121,131). During active inflammation the predominant form of HMGB1 is thought to be the disulfide bond C23 and C45 (disulfide-HMGB1); however, when inflammation begins to subside, HMGB1 is terminally oxidized at the cysteine residues rendering it biological inactive (oxidized-HMGB1) (6,121,135). Subsequently, an oxidizing environment following inflammation or injury may promote HMGB1 cytokine activity, instead of cellular repair by monocyte recruitment (121).…”
Section: Hmgb1 Releasementioning
confidence: 99%
“…Anti-HMGB1 monoclonal antibody [29] Anti-HMGB1 polyclonal antibody [28] Box A antagonist [28,30] Nuclear retention [24,27] Endotoxemia Inhibition of HMBG-1 release [31] CLP Anti-HMGB1 monoclonal antibody [34] Glucan phosphate (nuclear sequestering of HMGB1) [ Ischemia-reperfusion (kidney) Nuclear retention [37] Anti-HMGB1 polyclonal antibody [39] Ischemia-reperfusion (intestine) Anti-HMGB1 polyclonal antibody [41] Hepatoxicity Anti-HMGB1 polyclonal antibody [42] Pain Systemic injection of glycyrrhizin (binds to HMGB1) [43] Anti-HMGB1 polyclonal antibody [44,45] Islet transplantation Anti-HMGB1 monoclonal antibody [46] Atherosclerosis Anti-HMGB1 monoclonal antibody [47] Ischemia (brain) siRNA for HMGB1 [48] Anti-HMGB1 monoclonal antibody [49] Brain injury/damage to the blood-brain barrier Box A antagonist [50] Anti-HMGB1 monoclonal antibody [51] Intestinal tissue damage Anti-HMGB1 polyclonal antibody, nuclear retention [52] CLP, cecal ligation and puncture.…”
Section: Arthritismentioning
confidence: 99%